Greening Plant Participation through Assemblage Thinking - Ramos, Alfredo; Ganuza, Ernesto (Theoria (Pietermaritzburg), 2025)
The recent emergence of participatory and deliberative processes aimed at addressing the complexity of the ecological crisis has raised the questions of how to include the more-than-human in democracy and how new political relationships with the more-than-human can be established. To contribute to this discussion – focusing specifically on relationships with plants – this text explores potential dialogues between assemblage thinking and Critical Plant Studies. This dialogue is explored through the artistic installation The Plants Sense by Maria Castellanos and Alberto Valverde. The analysis of this installation demonstrates that assemblage thinking and Critical Plant Studies offer fruitful approaches for envisioning a democracy with plants. This approach is grounded in alternative ways of knowing and feeling that acknowledge the agency of plants and the capacities that emerge from assemblages.